Tracheobronchopathia osteochondroplastica: Case report and literature review. (2015) - Sun, Junping; Xie, Lixin; Su, Xianling; Zhang, Xingang
Abstract: Tracheobronchopathia osteochondroplastica (TPO) is a rare disorder characterized as multiple osseous or cartilaginous nodules in the submucosa of trachea and main bronchi. TPO remains an under recognized entity due to lack of awareness. Four cases of TPO are reported in this review as well as various facets of TPO description.